Natural resources: Curse or blessing? - Frederick van der Ploeg (Center for Economic Studies and ifo Institute (CESifo), 2010)
Are natural resources a 'curse' or a 'blessing'? The empirical evidence suggests either outcome is possible. The paper surveys a variety of hypotheses and supporting evidence for why some countries benefit and others lose from the presence of natural resources. These include that a resource bonanza induces appreciation of the real exchange rate, deindustrialization and bad growth prospects, and that these adverse effects are more severe in volatile countries with bad institutions and lack of rule of law, corruption, presidential democracies, and underdeveloped financial systems. Another hypothesis is that a resource boom reinforces rent grabbing and civil conflict especially if institutions are bad, induces corruption especially in non-democratic countries, and keeps in place bad policies. Finally, resource rich developing economies seem unable to successfully convert their depleting exhaustible resources into other productive assets. The survey also offers some welfare-based fiscal rules for harnessing resource windfalls in developed and developing economies.
Keywords: C12; C13; E01; F43; K42; O41; Q30; 330; resource curse; cross-country; panel and quasi-experimental evidence; Dutch disease; institutions; corruption; financial development; volatility; Hotelling rule; genuine saving; Hartwick rule; natural resource wealth management; sustainable development; Natürliche Ressourcen; Rohstoffressourcen; Dutch Disease; Wirtschaftswachstum; Institutionalismus; Hotelling-Regel; Nachhaltige Entwicklung; Vergleich; Welt; Entwicklungsländer; Industriestaaten